A forecasting approach for an evaluation of television set sector in Turkey - Ceyhan, Kemal. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 1987., 1987)
The government and corporate planners are facing sets of problem in identifying the promising industries, their market potential, future demand potential and future competitiveness. The purpose of this study is to investigate the television set sector in Turkey and evaluate future demand potential and future competitiveness of Turkish television sets. Chapter one gives some basic concepts about the product. chapter two examines the past history of the sector in the world as well as production and demand figures of TV sets in Turkey. Chapter three studies Turkish export and import figures for TV sets. Chapter four examines the demand prospects in Turkey by approaching the subject with cross sectional tools as well as domestic variables and domestic TV set demand functions. Demand figures until 1991 areestimafed in this chapter. Chapter five is a detailed analysis of the cost of a Turkish TV set produced under the licence of a foreign company in case of acceptance of agreed EEC custom duties of ANKARA agreement. Chapter six summarizes the findings of the study and states the :conclusions and implications. We conclude that although future TV set market in Turkey will be sufficient for the exploitation of the full capacity of the existing manufacturers, the sector will face serious threats in the future because of production technology and expected competition with the imported TV sets.
Keywords: Television broadcasting -- Turkey.